2020
DOI: 10.1534/g3.119.400771
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Approaches to Genotyping Repetitive DNA

Abstract: Individuals within a species can exhibit vast variation in copy number of repetitive DNA elements. This variation may contribute to complex traits such as lifespan and disease, yet it is only infrequently considered in genotype-phenotype associations. Although the possible importance of copy number variation is widely recognized, accurate copy number quantification remains challenging. Here, we assess the technical reproducibility of several major methods for copy number estimation as they apply to the large r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 82 publications
2
24
0
Order By: Relevance
“…The scenario that rDNA copy numbers have changed between samplings for low-and high-coverage data generation is unlikely as there are several reports documenting that rDNA copy number is largely stable in cell lines (23,24) . Taken together, our results are consistent with previous reports that different library preparations of the same samples often yield different rDNA copy number estimates (10) .…”
Section: Our Pipeline Reproduces Concerted Copy Number Variation Obsesupporting
confidence: 93%
See 4 more Smart Citations
“…The scenario that rDNA copy numbers have changed between samplings for low-and high-coverage data generation is unlikely as there are several reports documenting that rDNA copy number is largely stable in cell lines (23,24) . Taken together, our results are consistent with previous reports that different library preparations of the same samples often yield different rDNA copy number estimates (10) .…”
Section: Our Pipeline Reproduces Concerted Copy Number Variation Obsesupporting
confidence: 93%
“…However, eight additional rDNA copies seem unlikely to be biologically relevant, given an average copy number of ~250 . Moreover, we previously reported that rDNA copy number estimates based on short-read whole genome sequencing data can be error prone, with eight copies certainly being within the range of error (10) . Therefore, we sought to validate rDNA copy number in a subset of samples by alternate methods.…”
Section: Meaningful Concerted Copy Number Variation Is Not Present Inmentioning
confidence: 99%
See 3 more Smart Citations